Analysis of Strategic Planning, Innovation and Corporate Culture Towards SMEs Performance at Meatball SMEs in Sukabumi City - Alif Piya Nurul Hasanah; R.Deni Muhammad Danial; Faizal Mulia Z (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the influence of strategic planning, innovation, and corporate culture on the performance of  SMEs in the meatball culinary sector in Sukabumi City. The main problem raised in this study is the low performance of SMEs caused by weak strategic planning, lack of innovation, and corporate culture that has not been optimally formed. This study uses a quantitative approach with a descriptive causal method. The sample in this study consists of 156 meatball SMEs actors in Sukabumi City, selected using simple random sampling from a population of 255 business units. Data was collected through the distribution of questionnaires and analyzed using multiple linear regression, after undergoing validity, reliability, and classical assumption tests. Data processing was conducted using SPSS V.26 software. The results of the study indicate that strategic planning, innovation, and corporate culture have a positive and significant impact on SMEs performance. Therefore, it can be concluded that these three variables play a crucial role in enhancing the competitiveness and sustainability of SMEs. Consequently, it is recommended that SMEs operators consistently develop business strategies, innovate in their products, and foster a positive work culture.